Produto notável:
(3x/4 + 1)²
(3x/4-1)²
fguimara:
já resolveu?
Soluções para a tarefa
Respondido por
2
Vamos reduzir ao modelo:
![(a-b)^2=a^2-ab-ab+b^2=a^2-2ab+b^2 (a-b)^2=a^2-ab-ab+b^2=a^2-2ab+b^2](https://tex.z-dn.net/?f=%28a-b%29%5E2%3Da%5E2-ab-ab%2Bb%5E2%3Da%5E2-2ab%2Bb%5E2)
Então:
![(\frac{3x}{4})^2-2.\frac{3x}{4}.(-1)+(-1)^2=\frac{9x^2}{16}+\frac{3x}{2}+1 (\frac{3x}{4})^2-2.\frac{3x}{4}.(-1)+(-1)^2=\frac{9x^2}{16}+\frac{3x}{2}+1](https://tex.z-dn.net/?f=%28%5Cfrac%7B3x%7D%7B4%7D%29%5E2-2.%5Cfrac%7B3x%7D%7B4%7D.%28-1%29%2B%28-1%29%5E2%3D%5Cfrac%7B9x%5E2%7D%7B16%7D%2B%5Cfrac%7B3x%7D%7B2%7D%2B1)
Então:
Perguntas interessantes